2014
DOI: 10.5137/1019-5149.jtn.12852-14.2
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and histopathological effects of catechin on experimental peripheral nerve injuries

Abstract: This study shows that Catechin and its derivatives have a protective effect on peripheral nerve injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 34 publications
0
18
2
Order By: Relevance
“…According to the results, the molecular mechanism underlying the therapeutic impact of Cin on sciatic nerve damage may include the control of inflammatory and oxidant factors [Chao et al, 2008;Ho et al, 2013;Roghani et al, 2017]. Antioxidants such as Cin are promising to counteract the tissue-injuring influence of the inflammatory response [Yildirim et al, 2015]. This study also showed that Cin 30 is optimal therapeutically, and the other doses (Cin 10 and 90) could not have sufficient clinical impacts on sciatic nerve repair.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…According to the results, the molecular mechanism underlying the therapeutic impact of Cin on sciatic nerve damage may include the control of inflammatory and oxidant factors [Chao et al, 2008;Ho et al, 2013;Roghani et al, 2017]. Antioxidants such as Cin are promising to counteract the tissue-injuring influence of the inflammatory response [Yildirim et al, 2015]. This study also showed that Cin 30 is optimal therapeutically, and the other doses (Cin 10 and 90) could not have sufficient clinical impacts on sciatic nerve repair.…”
Section: Discussionmentioning
confidence: 80%
“…After a crush injury, endoneurial edema in the peripheral nerve affects the microenvironment by raising the pressure, lowering the blood flow, or altering the electrolyte concentration in the endoneurium. In the case of delayed restoration of adequate blood flow, ischemia causes wallerian axonal degeneration [Yildirim et al, 2015;Alvites et al, 2018], which takes place at the point of damage to the distal end of the nerve. It describes the axon demolition and its surrounding myelin, and limited degeneration exists just proximal to the injury [Atik et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…Four weeks later, all rats were deeply anesthesized (Ketamine hydrochloride 150 mg/kg) and specimens of the damaged sciatic nerves, including 0.5 cm proximal and distal nerve segments, were collected from the prior incision sites. At the end of the study, the rats were sacrificed (40).…”
Section: Anesthesia and Surgical Proceduresmentioning
confidence: 99%
“…Abnormal signals come not only from damaged axon but also from intact nociceptors that share the innervation of damaged nerves [3]. Peripheral nerve damage is common and important cause of long-term morbidity [4]. Upon exposure to nerve compression, the range of functional loss may oc-X.Z.…”
Section: Introductionmentioning
confidence: 99%